Separation of influenza virus‐like particles from baculovirus by polymer‐grafted anion exchanger. Issue 12 (30th April 2020) - Reiter, Katrin; Pereira Aguilar, Patricia; Grammelhofer, Dominik; Joseph, Judith; Steppert, Petra; Jungbauer, Alois
Abstract: The baculovirus expression vector system is a very powerful tool to produce virus‐like particles and gene‐therapy vectors, but the removal of coexpressed baculovirus has been a major barrier for wider industrial use. We used chimeric human immunodeficiency virus‐1 (HIV‐1) gag influenza‐hemagglutin virus‐like particles produced in Tnms 42 insect cells using the baculovirus insect cell expression vector system as model virus‐like particles. A fast and simple purification method for these virus‐like particles with direct capture and purification within one chromatography step was developed. The insect cell culture supernatant was treated with endonuclease and filtered, before it was directly loaded onto a polymer‐grafted anion exchanger and eluted by a linear salt gradient. A 4.3 log clearance of baculovirus from virus‐like particles was achieved. The absence of the baculovirus capsid protein (vp39) in the product fraction was additionally shown by high performance liquid chromatography‐mass spectrometry. When considering a vaccination dose of 10 9 particles, 4200 doses can be purified per L pretreated supernatant, meeting the requirements for vaccines with <10 ng double‐stranded DNA per dose and 3.4 µg protein per dose in a single step. The process is simple with a very low number of handling steps and has the characteristics to become a platform for purification of these types of virus‐like particles.